Pengaruh Kepemimpinan dan Pelatihan Terhadap Kompetensi Siswa Melalui Motivasi Pada Balai Latihan Kerja Komunitas Ponpes Gowa - Wahdi, Muh Sadikil; H, Hasanuddin; H, Hadiasman (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the influence of leadership and training on student competence through motivation at the Gowa PONPES Community Work Training Center. This study uses a quantitative approach by taking a population of 100 students of the Hidayatullah Gowa Islamic Boarding School Community Work Training Center and the Nurfadilah Gowa Community Work Training Center. The sampling technique used was total sampling, while the data analysis technique used path analysis. The results of the study showed that the Leadership variable with Motivation had a t-value of 4.237, while the t table was 1.661, p-value of 0.000 <? 0.05, the Training variable with Motivation had a t-value of 6.786, while the t table was 1.661, p-value of 0.000 <? 0.05, the Leadership variable with Competence had a t-value of 3.248, while the t table was 1.661, p-value of 0.000 <? 0.05, the Training variable with Competence had a t-value of 7.161, while the t table was 1.661, p-value of 0.000 <? 0.05, and the Motivation variable with Competence had a t-value of 4.774, while the t table 1.661, p value 0.000 < ? 0.05.